Legal Analysis of the Implementation of the Execution of the Object of Mortgage Based on Decree Number: 10/PDT.EKS/RL/2024/PN.JKT.BRT JO. Number 265/25/2023 - M. Aslam Fadli (Jurnal Kolaboratif Sains, 2025)
This study aims to analyze the validity of the execution of the object of mortgage based on Decree Number: 10/Pdt.Eks/RL/2024/PN.Jkt.Brt jo. The case was registered under the title of the Building Use Rights Certificate (SHGB) No. 265/25/2023/KPKNL, Area I Jakarta, with two Building Use Rights Certificates (SHGB) No. 11 and 12 in the name of PT Inasa Wahana. The execution was carried out due to the debtor's default, but this gave rise to legal issues because a third party, PT Lunto Richpat, was operating the property under a lease agreement without receiving any notification or warning prior to the execution. Furthermore, a discrepancy was found between the addresses of the property listed in the SHGB and the locations of the executed buildings, namely Jalan Bulak Teko, RT 006 RW 003 and RT 011 RW 003. This research employed a normative juridical method with a case approach and a statute approach. Data were obtained from court rulings, KPKNL auction documents, and legal literature on collateral. The results indicate that the execution did not fully comply with the principles of legal certainty and protection for third parties as stipulated in Law Number 4 of 1996 concerning Mortgage Rights. Mismatching the execution object and the lack of notification to third parties have the potential to create legal flaws in the execution process and civil liability for the execution applicant. The author recommends that every execution of mortgage rights be conducted with the prudential principle, thorough physical verification of the object, and official notification to interested parties, to ensure fairness and legal certainty for all parties involved.